Systematic Analysis of the Multiple Bioactivities of Green Tea through a Network Pharmacology Approach. (30th November 2014) - Zhang, Shoude; Shan, Lei; Li, Qiao; Wang, Xia; Li, Shiliang; Zhang, Yuan; Fu, Jianjun; Liu, Xiaofeng; Li, Honglin; Zhang, Weidong
Abstract : During the past decades, a number of studies have demonstrated multiple beneficial health effects of green tea. Polyphenolics are the most biologically active components of green tea. Many targets can be targeted or affected by polyphenolics. In this study, we excavated all of the targets of green tea polyphenolics (GTPs) though literature mining and target calculation and analyzed the multiple pharmacology actions of green tea comprehensively through a network pharmacology approach. In the end, a total of 200 Homo sapiens targets were identified for fifteen GTPs. These targets were classified into six groups according to their related disease, which included cancer, diabetes, neurodegenerative disease, cardiovascular disease, muscular disease, and inflammation. Moreover, these targets mapped into 143 KEGG pathways, 26 of which were more enriched, as determined though pathway enrichment analysis and target-pathway network analysis. Among the identified pathways, 20 pathways were selected for analyzing the mechanisms of green tea in these diseases. Overall, this study systematically illustrated the mechanisms of the pleiotropic activity of green tea by analyzing the corresponding "drug-target-pathway-disease" interaction network.